1×16 Rectangular dielectric resonator antenna array for 24 Ghz automotive radar system - Abderrahim Haddad; Mohssin Aoutoul; Mohamed Essaaidi; Khalid Sabri; Abdelaziz Khoukh; Youssef Errami; Anas Had; Fadwa El Moukhtafi; Redouane Jouali (Bulletin of Electrical Engineering and Informatics, 2022)
This paper presents the design of a 1×16-elements RDRA array for anti-collision radar SRR application at 24 GHz. A single RDRA with high dielectric constant of 41, fed by a simple microstrip line feeding technique, is initially designed to operate around 24 GHz. The RDRA element is further used within an array network structure made up of 16 linear antenna elements to cover the same frequency band. The simulated 1×16 RDRA array can reach a high gain, up to18.6 dB, very high radiation efficiency (97%), and ensure enough directional radiation pattern properties for radar applications with a 3-dB angular beam width of 6°. To validate our design, RDRA array’ radiation pattern computed results are compared to an equivalent fabricated patch antenna array reported in the literature.